The Difficulties of Reconstruction in The Achilles Area - Septrina, Rani; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: Scar management on the achilles region is also challenging due to its anatomical position, bony prominences, relatively limited skin, less subcutaneous fat, and less vascularization. Primary suture cannot be performed on the wide defect, whilst serial excisions are inapplicable to be done on a thick and tough scar. Wound healing in the lower limbs also typically get impaired due the gravitational effect on the venous system and the unlimited joint movement.Patient and Methods: A 21-year-old woman presented with a hard and thick hypertrophic scar on the achilles area due to deep dermal burns caused by hot metal two years ago. The patient had pruritic chronic ulcer on her scar. Scar excision was performed. In order to reduce the tension, a V-Y advancement flap was used to close the defect primarily. Foreslab was applied to reduce mobilization, and then continued by pressure garment application. On her next visit to the clinic, wound dehiscent was found. 10 days after the first excision, debridement was performed, wound re-sutured and dressed using topical honey covered by gauze.Result: Follow up results after 8 weeks showed a fully epithelialized wound. Compression bandage and limited mobility by foreslab application prevented the vertical growth of scar effectively. Patient no longer complaints about itchiness nor movement limitation.Summary: Planning surgical procedures for achilles reconstruction must take consider the followings: (1) choice of skin graft or flap, (2) choice of donor sites, (3) type of excision (4) hemostasis (5) fixation of skin grafts and splinting, and (6) dressings. Adjuvant preventive measures must also be implemented postsurgery to prevent regrowth of hypertrophic scar.